Influence of photopolymerization on propagation properties of photonic crystal fiber infiltrated with liquid crystal mixture - Kajkowska, Marta; Chychłowski, Miłosz; Lesiak, Piotr (Photonics Letters of Poland, 2022)
In this paper we analyze the influence of the photopolymerization process on propagation properties of photonic crystal fiber infiltrated with liquid crystal doped with a mixture of reactive monomer and photoinitiator. The obtained results showed changes in photonic band gap of the fiber due to refractive index change of the liquid crystal mixture caused by the polymerization process. Moreover, the research demonstrated the possibility of preserving the desired molecular orientation of liquid crystal initially stabilized by placing the sample in the external electric field. This was achieved by simultaneously irradiating the sample and controlling the orientation of liquid crystal molecules with the electric field. The spectral analysis of the polymerized sample showed no visible difference in propagation spectra when the electric field was turned off after the process was finished. Full Text: PDF References K. Yin et al., "Advanced liquid crystal devices for augmented reality and virtual reality displays: principles and applications", Light Sci Appl. 11, 161 (2022). CrossRef S. Singh, "Phase transitions in liquid crystals", Phys. Rep. 324, 107 (2000). CrossRef N. Tarjányi, M. Veveričík, D. Káčik, M. Timko, P. Kopčanský, "Birefringence dispersion of 6CHBT liquid crystal determined in VIS-NIR spectral range", Appl. Surf. Sci. 542, 148525 (2021). CrossRef R. Dąbrowski, P. Kula, J. Herman, "High Birefringence Liquid Crystals", Crystals 3, 443 (2013). CrossRef R. H. Self, C. P. Please, T. J. Sluckin, "Deformation of nematic liquid crystals in an electric field", Eur. J. Appl. Math. 13, 1 (2002). CrossRef T. Hegmann, H. Qi, V. M. Marx, "Nanoparticles in Liquid Crystals: Synthesis, Self-Assembly, Defect Formation and Potential Applications", J. Inorg. Organomet. Polym. 17, 483 (2007). CrossRef S. Kaur, S. P. Singh, A. M. Biradar, A. Choudhary, K. Sreenivas, "Enhanced electro-optical properties in gold nanoparticles doped ferroelectric liquid crystals", Appl. Phys. Lett. 91, 023120 (2007). CrossRef I. Dierking, "Polymer Network–Stabilized Liquid Crystals", Adv. Mater. 12, 167 (2000). CrossRef D. C. Hoekstra et al., "Wavelength-Selective Photopolymerization of Hybrid Acrylate-Oxetane Liquid Crystals", Angew. Chem. Int. Ed. 60, 10935 (2021). CrossRef Z. Ge, S. Gauza, M. Jiao, H. Xianyu, S.-T. Wu, "Electro-optics of polymer-stabilized blue phase liquid crystal displays", Appl. Phys. Lett. 94, 101104 (2009). CrossRef M. S. Chychłowski et al., "Locally-induced permanent birefringence by polymer-stabilization of liquid crystal in cells and photonic crystal fibers", Opto-electron. Rev. 26, 242 (2018). CrossRef R. Dąbrowski, J. Dziaduszek, T. Szczuciński, "Mesomorphic Characteristics of Some New Homologous Series with the Isothiocyanato Terminal Group", Mol. Cryst. Liq. Cryst. 124, 241 (1985). CrossRef